(3EXgGQ GdMb TQM MGTjI GdTjN GdjROj Ydi eJf GdJaJGRGfjs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3deG Yde (B..(3, Cj cfGjI hgj Cf jYHQ Yf TjA eYjf HdaX ZjQ UQjM aj GdOdGdI Ydjg HZQV gfGc cJYHjQ GdeGJf Yf chf cJGHg Ydi bSejf, GdbSe GdChd aj GdefWb hGdKGfj aj GdcdGes
(3BNQgG (B:s
(3BNQgG(B: (3bhdg(B: (3dCf GdebUhO ef GdYde Cj GdYde GdYedj, bhdg(B: (3GdYed(B: (3Cj GdYed HGdMb, bhdg aj GdCeQjf Cj GdYed hGdYde(B. (3hgPG eG CQOfG TQMg hGdSdGe hGdUdGI Ydi QShd Gddg(B.s
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs